Primary PCI in Diabetic Patients: Clinical Outcomes and Challenges - Shah , Hamid Ali; Khan, Muhammad Niaz; Waris, Abdul; Ali , Nasir; Saeed , Ihtisham; Muhammad Hafeez, (Indus Journal of Bioscience Research, 2024)
Objective: To evaluate clinical outcomes and procedural challenges in diabetic patients undergoing primary Percutaneous Coronary Intervention (PCI) for ST-segment elevation myocardial infarction (STEMI) at the Department of Cardiology, Hayatabad Medical Complex, Peshawar. Methodology: Conducted as an observational, single-center study from July 2022 to June 2023, 300 patients were enrolled, with equal numbers of diabetic and non-diabetic patients. Baseline demographics, clinical outcomes, and procedural success were analysed. Statistical tests included chi-square for categorical variables (major adverse cardiac events (MACE), stent thrombosis, restenosis, TIMI flow) and t-tests for age comparison. A significance level of p < 0.05 was set. Results: Diabetic patients had a mean age of 60.9 years compared to 59.9 years in non-diabetic patients (t = -0.41, p = 0.685). The distribution of MACE was similar between groups (χ² = 1.31, p = 0.727), as were rates of stent thrombosis (χ² = 0.00, p = 1.000) and restenosis (χ² = 0.85, p = 0.355). TIMI flow rates also showed no significant difference by diabetic status (χ² = 3.32, p = 0.190), indicating comparable outcomes between diabetic and non-diabetic patients. Conclusion: The study found no significant differences in primary PCI outcomes between diabetic and non-diabetic patients, suggesting that standardized procedural protocols may mitigate the heightened risk profile of diabetic patients. Multicenter studies with advanced diagnostic tools are recommended to enhance generalizability and optimize outcomes further in this population.